Tonic EEG dynamics during psychomotor vigilance task - Molina, Enrique; Correa, Angel; Sanabria, Daniel; Tzyy-Ping Jung (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
This study explored the EEG dynamics of participants performing a 45-minute long vigilance task. High-density EEG and subject responses were simultaneously recorded and analyzed using Independent Component Analysis and subsequent clustering of independent components. Time-frequency analysis was used to explore spectral differences in long versus short reaction time (RT) trials (i.e. trials with the fastest reaction times). Empirical results of this study showed that frontal beta and occipital alpha power increased as the RT's increased, consistent with our previous results in sustained-attention driving tasks.